Combined orthodontics and surgical approach to class III malocclusion with anterior open bite in adults (Indian Journal of Case Reports, 2019)
Skeletal anterior open bite with Class III malocclusion in adults is one of the most difficult malocclusions to treat. Surgical intervening is a must, along with orthodontics in such complex cases. The most effective treatment option in adult patients with Class III malocclusion and the skeletal anterior open bite is surgical repositioning of the maxilla or both jaws. The present case report describes the treatment protocol for Class III malocclusion with an anterior open bite in adult, a novel orthodontic- surgical approach. A 24-year old male patient with a Class III malocclusion, anterior open bite (skeletal), poor facial aesthetics, mandibular and chin protrusion. The objective was to achieve ideal overjet and overbite, to achieve class 1 incisor, canine and molar relation. To correct anterior open bite and achieve Class I skeletal jaw bases and to achieve esthetically pleasing profile and functionally stable occlusion. Therefore, by correction of the dental and skeletal jaw relationship, we hoped to improve the patient’s self- esteem, confidence and improved oral health quality of life.